26.2k views
5 votes
Given a≠±b and (a^2−b^2)/(a+b)=12, find a−b.

User GPB
by
4.9k points

2 Answers

4 votes


a\\eq\pm b\Rightarrow \frac{ ( {a}^(2) - {b}^(2) ) }{a + b} = 12\Leftrightarrow ((a - b)(a + b))/(a + b) = 12\Leftrightarrow a - b = 12

User Tooluser
by
5.3k points
4 votes

Answer:

Explanation:

a^2 - b^2 factors into (a + b)(a - b)

So now you have

(a + b)(a - b)

========== = 12

(a + b)

You are given that a <> b

So a + b cancels with (a + b) on the top.

a - b = 12

User Quint
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.